DETECTION OF CAUSATIVE AGENTS OF SEXUALLY TRANSMITTED DISEASES IN SYMPTOMATIC INFERTILE WOMEN USING REAL TIME PCR TECHNIQUE - QASIM , VAMAN Q; SAEED, ALI YHAY (Journal of Duhok University, 2023)
Sexually transmitted infections or venereal diseases constitute a major health problem especially in developing countries, including Iraq with complications like pelvic inflammatory disease, ectopic pregnancy, cervical cancer, infertility, and congenital infections. The main goal of current study is to detect the common bacterial causes of sexually transmitted infections among symptomatic infertile women using real time PCR technique. A cross-sectional study was conducted from February 2022 to February 2023. A total of 100 vaginal swabs were collected from symptomatic infertile women with ages ranging from 20 to 49 years (mean 23.97 years ±6.90 SD) who attended the private health centers in Duhok, Kurdistan Region, Iraq. The vaginal swabs were collected from each patient and processed by real time PCR to detect C. trachomatis, T. vaginalis, N. gonorrhoeae, M. genitalium, M. hominis, U. urealyticum and U. parvum. Out of 100 symptomatic infertile women, 68 were positive for one or more of the causative agents. The highest rate of infection was caused by U. parvum (50%), followed by M. homonis (21.0%), U. urealyticum (16.0%) and the lowest percentage was 1.00% for C. trachomatis, while all samples were negative for N. gonorrhoeae, T. vaginalis and M. genitalium. No significant association was found between C. trachomatis, M. hominis, U. urealyticum and U. parvum with age groups, duration of infertility and levels of education of studied symptomatic infertile women except C. trachomatis which showed significant association (p=0.001) with duration of infertility from 11-16 years. Prevalence of M. hominis, U. urealyticum and U. parvum in the birth canal of infertile women demands more studies because several studies in the world highlighted on the presence of association between these colonized bacteria and infertility due to the tubal damage or blockage